Design of Character Building for Learners in Boarding Schools in West Sumatera - Muswara, Aulia; Zalnur, Muhammad (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2019)
This study aims to see how the school management in developing the character of students in one of the boarding school in West Sumatera. This study uses qualitative methods with a case study approach. Sources of data were taken to 38 informants consisting of 8 elements of the school namely the principal, teacher, boarding supervisor, security and cleaning service, canteen keeper, students and parents. All data obtained by in-depth interviews with all informants, the authors also took data through direct observation at the research site. Overall the results of the study show that there are seven character values instilled by the school, namely religious character, curiosity, discipline, confidence, responsibility, independence and honesty. The seven character values are instilled through twelve activities such as tahsin and tahfidzd Al-Quran, worship services, prayers in congregation, learning clinics, training and guidance, Arabic and English communication programs in the dormitory, motivation, joint sports, mutual cooperation and daily activities. Character building design as implemented by the school, it turns out that it is able to change the behavior of students in a more positive direction such as manners, discipline, obedience to worship, obedient to the rules, clean and tidy life, daring to appear, regular life, and honest behavior. This means that the school has succeeded in fostering the character education of students through various activities and all these activities are well planned by the cooperation of all elements of the school. The author considers the design to be emulated by other schools as a guide in fostering the character of students